Contextualization of the Tarbawi Hadith on Student Character Education in the Society 5.0 Era - Maslani, Maslani; Saadah, Susi; Aldi, Ujang; Darojat, Darojat; Hidayat, Agus; Arjuna, Arjuna (Jurnal Iman dan Spiritualitas, 2025)
This study investigates the contextualization of Hadits Tarbawi as a framework for character education among students in the era of Society 5.0, where the convergence of artificial intelligence, big data, and hyperconnectivity reshapes educational paradigms. The study aims to critically examine how prophetic values particularly honesty, responsibility, emotional regulation, and moral exemplarity can be meaningfully implemented in a digitized learning environment to form spiritually grounded and emotionally resilient individuals. Using a descriptive-qualitative approach and content analysis methodology, the research draws on classical Islamic texts, empirical studies, and interdisciplinary theories on technology and pedagogy. Findings show that the integration of Hadits Tarbawi with digital tools such as Brain Emotional Learning Controllers (BELC), AI-based emotion detection systems, and technology-rich learning environments significantly enhances students' moral cognition and emotional intelligence. Moreover, spiritual practices such as habitual prayer, self-reflection, and prophetic storytelling remain indispensable in anchoring values amidst the noise of digital culture. The study concludes that a hybrid educational model combining Islamic prophetic pedagogy and adaptive digital strategies offers a viable and ethically sound solution to address moral degradation and identity crises among Muslim youth. Theoretically, the research contributes to the field of Islamic education by reaffirming the relevance of Hadits Tarbawi in modern pedagogy. Practically, it provides an innovative model for character education that leverages technological advancement without compromising spiritual depth. This hybrid model aligns with global trends in spiritual-tech integration, promoting an educational ethos that is human-centered, value-driven, and future-oriented.